2019
DOI: 10.3389/fgene.2019.00272
|View full text |Cite
|
Sign up to set email alerts
|

A QTL for Number of Teats Shows Breed Specific Effects on Number of Vertebrae in Pigs: Bridging the Gap Between Molecular and Quantitative Genetics

Abstract: Modern breeding schemes for livestock species accumulate a large amount of genotype and phenotype data which can be used for genome-wide association studies (GWAS). Many chromosomal regions harboring effects on quantitative traits have been reported from these studies, but the underlying causative mutations remain mostly undetected. In this study, we combine large genotype and phenotype data available from a commercial pig breeding scheme for three different breeds (Duroc, Landrace, and Large White) to pinpoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 51 publications
11
45
0
Order By: Relevance
“…Using the pipeline, ( Derks et al in preparation) identified causal variants that are already known in literature to affect complex traits in pigs. For example, they found a variant in the MC4R gene that is already known to affect production traits in pigs (Kim et al 2000), a causal variant in the VRTN gene affecting the number of teats in pigs (Van Son et al 2019), and a causal variant in the PRKAG3 gene affecting meat quality (Milan et al 2000). In addition to enhancing our understanding of the biology of complex traits, the pipeline can be used to pre-select likely causal variants that can continuously be added on to the array for GP.…”
Section: Pre-selection Of Variants Using Other Methodsmentioning
confidence: 99%
“…Using the pipeline, ( Derks et al in preparation) identified causal variants that are already known in literature to affect complex traits in pigs. For example, they found a variant in the MC4R gene that is already known to affect production traits in pigs (Kim et al 2000), a causal variant in the VRTN gene affecting the number of teats in pigs (Van Son et al 2019), and a causal variant in the PRKAG3 gene affecting meat quality (Milan et al 2000). In addition to enhancing our understanding of the biology of complex traits, the pipeline can be used to pre-select likely causal variants that can continuously be added on to the array for GP.…”
Section: Pre-selection Of Variants Using Other Methodsmentioning
confidence: 99%
“…The impact of the splice mutations on the expression of the gene was assessed using RNA-seq data. The animals sequenced are frequently used artificial insemination boars selected based on extreme phenotypes all present in the genotyping data (van Son et al 2017b). The phenotypes are based on high and low sperm DNA fragmentation index, a measure of well packed double-stranded DNA vs singlestranded denatured DNA, which is an important indicator of boar fertility.…”
Section: Rna Sequencing and Nonsense Mediated Decaymentioning
confidence: 99%
“…The combination of genotype and gene expression data provides an additional layer of evidence to find causal variation, as differences in expression of genes can be associated with a variant (expression quantitative trait loci; eQTL). In this study we use 59 RNA-sequenced samples (van Son et al 2017b) from Landrace (n=34) and Duroc (n=25) to test for differential expression between the genotype classes (homozygous reference, heterozygous, homozygous alternative) to associate the expression of genes with the genotypes. The samples were sequenced from testis tissue and further details about the sequenced samples and alignment depth are provided in Table S2.…”
Section: Gene Expression Information Allows Identification Of Possiblmentioning
confidence: 99%
See 2 more Smart Citations